Low Power and Low Complexity Flip-Flop Design using MIFGMOS - Ragavendran, U; Ramachandran, M (International Journal of Engineering and Technology, 2018)
Sequential logic is essential in many applications as data processing for speech recognition in cochlear implants. In this paper, a family of latches based on floating-gate MOS (FGMOS) transistors is presented. This family takes advantage on the fact that FGMOS logics process data using mostly passive devices, achieving small area and low-power, requirements of modern electronics. Post-layout SPICE simulations from an ON-Semiconductors 0.5 µm CMOS process technology shows improvements over conventional CMOS logic families, making FGMOS latches ideal for low-power applications.